The Effect Of Yeast (Saccharomyces cerevisiae) Addition In Feed To The Growth Of The Silver Pompano (Trachinotus Blochii) (Jurnal Intek Akuakultur, 2020)
Silver pompano is a seawater fish commodity that has been successfully developed in Indonesia, one of which is Batam Aquaculture Fisheries Center. The purpose of this study was to determine the effect and dose of yeast on the growth of Silver pompano (Trachinotus blochii) seeds. This research was conducted from May to June 2019 at the Wet Laboratory of the Faculty of Marine and Fisheries Sciences, Raja Ali Haji Maritime University. This research was conducted with a Completely Randomized Design (CRD) method with 4 treatments and 3 replications, treatment A or control without adding yeast, treatment B (adding 5gr yeast / kg of feed), treatment C (adding 10gr yeast / feed yeast), and treatment D (addition of yeast 15gr / kg of feed). Data were analyzed by Anova One-Way and if the results of the Anova One-Way test showed a significant effect (P> 0.01) then it would be continued with Duncan test, the results of the study would be displayed in the form of graphs, tables, and documentation. Research parameters include absolute weight growth, absolute length growth, daily growth and water quality. The best results in this study were in treatment C with the addition of yeast 10gr / kg of feed. In the absolute weight growth parameter of 0.70 ± 0.09b, absolute length growth of 0.735 ± 0.02c , feed convertion ratio 4,62±0,56c, efficient use of feed 21,83±2,59b and survival rate 96,30±6,41. These results indicate that the addition of yeast into the feed can accelerate the growth of the Silver pompano (Trachinotus blochii).